The Effectiveness of Math Magazine Assisted Problem Based Learning on Students’ Problem Solving Viewed from Learning Independence - Azizah, Maharani Nuur; Kartono, Kartono (Unnes Journal of Mathematics Education, 2023)
Problem solving ability is one of the abilities that must be possessed by students of the five abilities in mathematics education. The problem-solving ability and independent learning character of SMA Negeri 5 Semarang students still need to be improved. One of the efforts to enhance problem-solving skills and the character of learning independence is to apply Problem Based Learning with the help of Math Magazine. This research aims (1) to test the effectiveness of Problem Based Learning assisted by Math Magazine and (2) to describe problem solving abilities with Problem Based Learning assisted by Math Magazine in terms of learning independence. This research used a mixed method research method with a sequential explanatory research design. The population in this study were students of class XI SMA Negeri 5 Semarang for the 2022/2023 academic year. The selected sample was 33 students in the experimental group and 28 students in the control group. Data collection methods were carried out by tests, independent learning questionnaires, and interviews. The results showed that (1) Problem Based Learning assisted by Math Magazine on the ability to solve problems exceeds classical completeness by 91%, (2) The average problem solving ability in the Problem Based Learning model assisted by Math Magazine is better than the problem solving abilities of control class students, and (3) the average problem solving ability in the Problem Based Learning model assisted by the Math magazine is more than 70.